The Influence of Packaging, Flavour Variants, Perceived Quality on Purchasing Decisions for Maros Salenrang Bread - Risna; Hasnidar; Irwan, Andi Muhammad; Rahman, Sundari (Candela Edutech Indonesia, 2025)
In the food industry, especially in Micro, Small, and Medium Enterprises (MSMEs) or Small and Medium-sized Enterprises (SMEs) sector, understanding consumer behavior is a vital element in marketing strategy. This study aims to analyze the influence of packaging, flavor variants, and quality perceptions on consumer purchasing decisions on Maros Salenrang Bread products in Maros Regency. With a quantitative approach. The sampling was done by distributing questionnaires where the population was all consumers of Maros Salenrang bread with a sample of 96 respondents through the snowball sampling method and analyzed using SPSS version 26. Descriptive analysis was used in this investigation. Instruments including validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, determination coefficient test (r2), partial t test, and simultaneous f test were applied to test respondents' questionnaire responses. The results showed that the three independent variables packaging, flavor variants, and quality perceptions had a significant effect both partially and simultaneously on purchasing decisions